Implementación de un prototipo de hormigón permeable para evitar inundación en la Avenida 39, sector Norte de Guayaquil - Castro Piguave, Bernie David (2025)
The practical case presented in the document deals with the design of a permeable concrete prototype that will serve to prevent flooding on 39th Avenue, in the northern sector of Guayaquil. The main objective is to evaluate the technical, economic and environmental viability of this material as a sustainable solution for the management of rainwater in the aforementioned sector...........